Meningkatkan Hasil Belajar Siswa Pelajaran PKn Model Kooperatif Tipe Tebak Kata di Hulu Sungai Selatan - Lisnawati (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to describe and analyze the learning process of citizenship education on the subject of Pancasila through cooperative learning models of the charades type which can improve the learning outcomes of class I students at Madrasah Ibtidaiyah Negeri 12 Hulu Sungai Selatan. This research is a Classroom Action Research (PTK) which is carried out collaboratively between teachers and researchers. The subjects of this study were first grade students at Madrasah Ibtidaiyah Negeri 12 Hulu Sungai Selatan, which consisted of 14 students, consisting of 6 male students and 8 female students. Data was collected through observation, interviews, documentation and tests.This research consisted of two cycles, namely Cycle I and Cycle II. The results showed that the use of the charades type cooperative learning model was effective in increasing student interest and achievement in the subject of Citizenship Education. This can be seen from the increase in the percentage of students' interest in the sound of Pancasila material during learning, namely 33.33% in the less category in the pre-cycle, 50% in the medium category in cycle I, and 90% in the very good or high category in cycle II. This shows that the charades type cooperative learning model has a positive effect on increasing student learning outcomes in Civics learning. It can be concluded that there is an increase in each research cycle based on the results obtained.